An analysis of the censorship of popular music within the context of cultural struggle in South Africa during the 1980s - Drewett, Michael (Rhodes University, Faculty of Humanities, Department of Sociology and Industrial Sociology, 2004)
The censorship of popular music in South Africa during the 1980s severely affected South African musicians. The apartheid government was directly involved in centralized state censorship by means of the Directorate of Publications, while the South African Broadcasting Corporation exercised government censorship at the level of airplay. Others who assisted state censorship included religious and cultural interest groups. State censorship in turn put pressure on record companies, musicians and others to practice self-censorship. Many musicians who overtly sang about taboo topics or who used controversial language subsequently experienced censorship in different forms, including police harassment. Musicians were also subject to anti-apartheid forms of censorship,such as the United Nations endorsed cultural boycott. Not all instances of censorship were overtly political, but they were always framed by, and took place within, a repressive legal-political system. This thesis found that despite the state's attempt to maintain its hegemony, musicians sought ways of overcoming censorship practices. It is argued that the ensuing struggle cannot be conceived of in simple binary terms. The works of Antonio Gramsci, Michel Foucault and Pierre Bourdieu, in particular, are applied to the South African context in exploring the localized nuances of the cultural struggle over music censorship. It is argued that fragmented resistance to censorship arose out of the very censorship structures that attempted to silence musicians. Textual analysis brought to light that resistance took various forms including songs with provocative lyrics and titles, and more subtle means of bypassing censorship, including the use of symbolism, camouflaged lyrics, satire and crossover performance. Musicians were faced with the challenge of bypassing censors yet nevertheless conveying their message to an audience. The most successful cases negotiated censorial practices while getting an apparent message across to a wide audience. Broader forms of resistance were also explored, including opposition through live performance, counter-hegemonic information on record covers, resistance from exile, alignment with political organizations and legal challenges to state censorship. In addition, some record companies developed strategies of resistance to censorship. The many innovative practices outlined in this thesis demonstrate that even in the context of constraint, resistance is possible. Despite censorship, South African musicians were able to express themselves through approaching their music in an innovative way.
Keywords: Censorship -- South Africa; Popular music -- Censorship -- South Africa; Popular music -- Censorship -- South Africa -- History; Popular music -- Social aspects -- South Africa; Popular music -- Political aspects -- South Africa; Popular music -- South Africa -- History and criticism; Protest songs -- South Africa -- History and criticism